1968
DOI: 10.1017/s0021859600014672
|View full text |Cite
|
Sign up to set email alerts
|

The influence of intake of dietary energy in pregnancy and lactation upon sow productivity

Abstract: Fifty-two Large White gilts, arranged in thirteen groups of four litter sisters, were allocated at mating to one of four treatment groups. These treatments, arranged as a 2x2 factorial, allowed daily energy intakes in pregnancy of 8-3 Meal (H(e)) or 5-2 Meal (L(e)) and of average daily intake during lactation of 20 Meal (h(e)) or 13-8 Meal (m(e)). Daily intakes of protein, minerals and vitamins were similar for all treatments. There were no consistent differences in health or breeding regularity between the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0
1

Year Published

1982
1982
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 4 publications
5
15
0
1
Order By: Relevance
“…As expected, sows fed Lo lost more (P<.01) weight during lactation than those fed Hi. These results agree with those of Elsley et al (1968), O'Grady et al (1975) and Reese et al (1982). Average litter size at weaning was not affected by energy intake which also agrees with previous reports (Elslcy et al, 1968;O'Grady et al, 1973;Reese et al, 1982).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…As expected, sows fed Lo lost more (P<.01) weight during lactation than those fed Hi. These results agree with those of Elsley et al (1968), O'Grady et al (1975) and Reese et al (1982). Average litter size at weaning was not affected by energy intake which also agrees with previous reports (Elslcy et al, 1968;O'Grady et al, 1973;Reese et al, 1982).…”
Section: Resultssupporting
confidence: 93%
“…Apparently sows fed Lo compensated for their greater weight loss during Lac 1 [indicated by the differences (P<.01) in Lac 1 sow weaning weight]. Previous reports indicate that energy intake (Elsley et al, 1968;Adam and Shearer, 1975;O'Grady et al, 1975) and feed intake (Lodge et al, 1961;Elsley et al, 1969;Hitchcock et al, 1971) during lactation had no effect on net sow weight change during gestation. However, MacPherson et al (1969) and O'Grady (1971) reported that sows fed low protein diets during lactation tended to compensate by gaining more weight during the following gestation than those fed higher protein diets.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations